A study on environment public spending - Wellington Bueno; Fernando Oliana; Benilson Borinelli (Economia & Região, 2013)
This text deals with the importance of studying environment public spending. Initially, we discuss the concept of environment public spending and how it became a public accounting function. Later, an analysis of several studies on the theme was carried out to promote a discussion on the environment public funds allocated by governments. Next, a discussion on the relevance of the theme and the need for further studies is presented, since investments on environment management still need to be better allocated and duly dimensioned. Currently, transparence in public spending has promoted the realization of more studies, leading to a more careful observation of environmental issues by the society, showing that these issues still need more attention from the goverment.